2016
DOI: 10.11646/bde.38.1.3
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Centres of moss diversity in southern Africa</strong></p>

Abstract: Moss diversity in southern Africa is greatest in the Cape Fold Mountains of the southwestern Cape, and the Drakensberg mountains along the Great Escarpment of KwaZulu-Natal, Mpumalanga and Limpopo Provinces of South Africa. Five main, and five secondary centres of moss diversity are described, based on the number of moss species per half degree grid square in southern Africa (South Africa, Namibia, Botswana, Lesotho and Swaziland). The main centres are the Southwestern Cape, outeniqua, Amathole, KwaZulu-Natal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Quantitative measures mapped for land snail species richness and endemism reveal similar patterns ( Fig 5 ), with higher values along the south-eastern coastal belt and on the south-eastern escarpment, especially its eastern aspects towards the coastal belt, similar to those for millipedes [ 94 , 95 ], vertebrates [ 24 ], bryophytes [ 96 ] and higher plants [ 20 ]. The Highveld and Bushveld provinces are generally species- as well as endemic-poor, although the Bushveld supports more land snail endemics compared to the Highveld ( Fig 5E ), which could possibly be attributed to the comparatively higher habitat heterogeneity in the Bushveld that provide sheltering microhabitats into which snails can retreat, supported by the higher spatial area covered by Bushveld, and again to the supposedly stable and milder climate in the Bushveld (see the role of forests discussed above) compared to that of the Highveld characterized by drought, frost, waterlogging and wildfire causing its treelessness [ 97 ].…”
Section: Discussionmentioning
confidence: 80%
“…Quantitative measures mapped for land snail species richness and endemism reveal similar patterns ( Fig 5 ), with higher values along the south-eastern coastal belt and on the south-eastern escarpment, especially its eastern aspects towards the coastal belt, similar to those for millipedes [ 94 , 95 ], vertebrates [ 24 ], bryophytes [ 96 ] and higher plants [ 20 ]. The Highveld and Bushveld provinces are generally species- as well as endemic-poor, although the Bushveld supports more land snail endemics compared to the Highveld ( Fig 5E ), which could possibly be attributed to the comparatively higher habitat heterogeneity in the Bushveld that provide sheltering microhabitats into which snails can retreat, supported by the higher spatial area covered by Bushveld, and again to the supposedly stable and milder climate in the Bushveld (see the role of forests discussed above) compared to that of the Highveld characterized by drought, frost, waterlogging and wildfire causing its treelessness [ 97 ].…”
Section: Discussionmentioning
confidence: 80%
“…According to the available literature and data from the main South African public fungarium (PREM), bryophilous Pezizales are completely unknown from southern Africa, despite the fact that this is a large and species-rich region, which hosts a very diverse bryoflora (Van Rooy and Phephu 2016). Our initial work revealed that this group of fungi is relatively common and probably also very diverse in southern Africa, despite the fact that the work was carried out in extraordinarily dry (and thus unsuitable) summer.…”
Section: Discussionmentioning
confidence: 99%